Twisted magnetic field in star formation processes of L1521 F revealed by submillimeter dual-band polarimetry using the James Clerk Maxwell Telescope. (9th January 2023) - Fukaya, Sakiko; Shinnaga, Hiroko; Furuya, Ray S; Tomisaka, Kohji; Machida, Masahiro N; Harada, Naoto
Abstract: Understanding the initial conditions of star formation requires both observational studies and theoretical works taking into account the magnetic field, which plays an important role in star formation processes. Herein, we study the young nearby dense cloud core L1521 F [ n (H2 ) ∼10 4−6  cm −3 ] in the Taurus Molecular Cloud. This dense core hosts a 0.2  M ⊙ protostar, categorized as a very low luminosity object with complex velocity structures, particularly in the vicinity of the protostar. To trace the magnetic field within the dense core, we conducted high-sensitivity submillimeter polarimetry of the dust continuum at λ = 850 μm and 450 μm using the POL-2 polarimeter situated in front of the SCUBA-2 submillimeter bolometer camera on the James Clerk Maxwell Telescope. This was compared with millimeter polarimetry taken at λ = 3.3 mm with ALMA. The magnetic field was detected at λ = 850 μm in the peripheral region, which is threaded in a north–south direction, while the central region traced at λ = 450 μm shows a magnetic field with an east–west direction, i.e., orthogonal to that of the peripheral region. Magnetic field strengths are estimated to be ∼70 μG and 200 μG in the peripheral and central regions, respectively, using the Davis–Chandrasekhar–Fermi method. The resulting mass-to-flux ratio of three times larger than that of magnetically critical state for both regions indicates that L 1521 F is magnetically supercritical, i.e., gravitational forces dominate over magnetic turbulence forces. Combining observational data with magnetohydrodynamic simulations, detailed parameters of the morphological properties of this puzzling object are derived for the first time.